Autonomous robot-driven deliveries: A review of recent developments and future directions. (September 2022) - Srinivas, Sharan; Ramachandiran, Surya; Rajendran, Suchithra
Abstract: The adoption of autonomous delivery robots (ADRs) across various delivery applications has rapidly accelerated in recent years. This growth can be attributed to advancements in technology and legislation, exacerbated conventional delivery challenges, and pandemic-mediated need for contactless deliveries. A growing number of studies have investigated the various aspects pertaining to ADR-based delivery operations. Nevertheless, there is a lack of extensive literature review that holistically reports on various problems in ADR-based delivery operations, adopted methodologies, novel findings, and future needs. This paper aims to systematically survey the existing research on ADR-based delivery systems and associated operations. Foremost, we discuss various technology, design, and legal factors that impact ADR operations. Subsequently, we are the first to review the state-of-the-art research in ADR-based deliveries concerning the following areas—routing, infrastructure and fleet planning, factors affecting efficiency, technology acceptance, and social intelligence. Finally, we anticipate potential challenges from an operations management perspective, identify research gaps, and delineate future research opportunities for ADR-based deliveries. Highlights: Autonomous delivery robots (ADR) are expected to transform last-mile logistics. ADR could improve delivery efficiency in terms of time, cost and sustainability. First study to review practical and research developments on ADR operations. Potential challenges with ADR operations are also reviewed. Future research directions for enhancing ADR delivery efficiency are presented.